Identification of a Region of the Tobacco Mosaic Virus 126- and 183-Kilodalton Replication Proteins Which Binds Specifically to the Viral 3′-Terminal tRNA-Like Structure - Osman, T. A. M. (American Society for Microbiology, 2003)
UV irradiation of a mixture of an isolated tobacco mosaic virus (TMV; tomato strain L [TMV-L]) RNA-dependent RNA polymerase complex and the TMV-L RNA 3′-terminal region (3′-TR) resulted in cross-linking of the TMV-L 126-kDa replication protein to the TMV-L 3′-TR. Using both Escherichia coli-expressed proteins corresponding to parts of the 126-kDa protein and mutants of the 3′-TR, the interacting sites were located to a 110-amino-acid region just downstream of the core methyltransferase domain in the protein and a region comprising the central core C and domain D2 in the 3′-TR. Mutation to alanine of a tyrosine residue at position 409 or a tyrosine residue at position 416 in the protein binding region abolished cross-linking to the 3′-TR, and corresponding mutations introduced into TMV-L RNA abolished its ability to replicate in tomato protoplasts, with no detectable production of either plus- or minus-strand RNA. The results are compatible with a model for initiation of TMV-L minus-strand RNA synthesis in which an internal region of the TMV-L 126-kDa protein first binds to the central core C and domain D2 region of the TMV-L 3′-TR and is then followed by binding of the 183-kDa protein to this complex and positioning of the catalytically active site of the polymerase domain close to the 3′-terminal CCCA initiation site.